Technical characteristics of elite youth female soccer match-play: position and age group comparisons between under 14 and under 16 age groups - Harkness-Armstrong, A.; Till, K.; Datson, N.; Emmonds, S. (International Journal of Performance Analysis in Sport, 2020)
The purpose of this study was to quantify the technical characteristics of U14 and U16 elite youth female soccer match-play and compare position-specific differences between and within these age groups. A total of 449 match observations from 45 matches were undertaken on 189 players representing Regional Talent Centres in The Football Association`s Girls` England Talent Pathway league. Linear mixed modelling determined position-specific differences for 24 technical and 4 possession-based variables. Results showed similar team possession-based characteristics at both age groups. Interceptions (U14 = 4.6 ± 0.3, U16 = 3.9 ± 0.3) and tackles (U14 = 4.2 ± 0.3, U16 = 3.2 ± 0.3) were the most common defensive actions. Passes were the most common offensive action (U14 = 21.8 ± 1.8, U16 = 25.1 ± 1.9). In possession, U14 central players performed more actions than wide players, whilst actions were more evenly distributed amongst positions at U16, suggesting a variation in playing style between age groups. Technical performances of players were position-dependent, and differences in offensive and defensive variables were observed between age groups across all positions. These findings may assist practitioners in informing specific coaching practice, training programme design or talent identification processes within this population.